The suitability of using death certificates as a data source for cancer mortality assessment in Turkey - Ulus, Tumer (Croatian Medical Schools, 2012)
AIM: To compare the quality of the 2008 cancer mortality data of the Istanbul Directorate of Cemeteries (IDC) with the 2008 data of International Agency for Research on Cancer (IARC) and Turkish Statistical Institute (TUIK), and discuss the suitability of using this databank for estimations of cancer mortality in the future. METHODS: We used 2008 and 2010 death records of the IDC and compared it to TUIK and IARC data. RESULTS: According to the WHO statistics, in Turkey in 2008 there were 67 255 estimated cancer deaths. As the population of Turkey was 71 517 100, the cancer mortality rate was 9.4 per 10 000. According to the IDC statistics, the cancer mortality rate in Istanbul in 2008 was 5.97 per 10 000. CONCLUSION: IDC estimates were higher than WHO estimates probably because WHO bases its estimates on a sample group and because of the restrictions of IDC data collection method. Death certificates could be a reliable and accurate data source for mortality statistics if the problems of data collection are solved.